MONITORING THE DEGRADATION OF PASTURE PLANT COVER NORTH-WESTERN KYZYLKUM BASED ON ANALYSIS NDVI MEAN SPACE SHOOT LANDSAT (Web of Technology: Multidimensional Research Journal, 2025)
This article presents the results of studies on the real ecological and economic condition of the main types of pastures of the North-Western Kyzylkum and the degree of vegetation degradation, using satellite imagery, and determining the degree of territory degradation depending on vegetation indices based on the results of geobotanical monitoring of these changes. The application of the NDVI vegetation index allows for a quantitative assessment of the development of plant green mass during the growing season.